2009
DOI: 10.1007/s00383-009-2329-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of surgery for malignant sacrococcygeal teratoma: 20-year experience of a regional UK centre

Abstract: Surgery for malignant sacrococcygeal teratoma is safe and has a low complication rate. The long-term outcomes are favourable with minimal side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…This lack of surveillance may be due to some published series minimizing the risk of urologic co‐morbidity. For example, Khalil et al reported that only 1 of 12 (8.3%) patients suffered any urologic complications. However, this study, as with many others, lacks any description of how the authors assessed urologic co‐morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of surveillance may be due to some published series minimizing the risk of urologic co‐morbidity. For example, Khalil et al reported that only 1 of 12 (8.3%) patients suffered any urologic complications. However, this study, as with many others, lacks any description of how the authors assessed urologic co‐morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative monitoring is also necessary ( 19 ), as the possibilities of recurrence and malignant transformation exist. The probability of malignant transformation reportedly increases with age ( 20 ); as such, regular CT and physical examinations should be performed to detect any progression in residual teratoma tissue over the course of the patient's life ( 20 ). To that end, alpha-fetoprotein is a sensitive serum marker that can be used to screen for teratoma recurrence, as well as the severity thereof ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…A per-rectal examination was performed to rule out a fecaloma, and a mass posterior to rectum was identified. A literature search on PubMed and Google unearthed several reports wherein sacrococcygeal teratomas have been mistaken for lesions such as hemangiomas,[11] meningomyeloceles,[1213] vertebral disc prolapse,[12] abscesses,[1214] fecal or perianal fistula,[12] cloaca, and fistula-in-ano or inguinal lymphadenitis. [12] The vice-versa is also true with lesions such as extraspinal sacrococcygeal ependymoma,[15] genitourinary plexiform neurofibroma[16] and congenital infantile fibrosarcoma[17] masquerading as sacrococcygeal teratoma.…”
Section: Discussionmentioning
confidence: 99%